Measurement of the speed of leak noise propagation in buried water pipes: Challenges and difficulties - Brennan, Michael John [UNESP]; de Almeida, Fabrício Lobato César [UNESP]; de Lima, Fábio Kroll [UNESP]; Castillo, Pedro Christian Ayala [UNESP]; Paschoalini, Amarildo Tabone [UNESP] (Springer Nature, 2018)
To accurately determine the position of a leak in a buried plastic water pipe using acoustic correlation, a good estimate of the speed of noise propagation (wave speed) is required. The factors that affect this wave speed, and attenuation of the wave as it propagates along the pipe, include the pipe flexibility and the soil properties. These effects are discussed in this paper, and are illustrated by way of simulations for two different pipe sizes and two different soil types. It is shown that the soil type in Brazil can have a profound effect on the wave speed and hence the accuracy of leak location. Some practical problems in estimating the wave speed from in-situ measurements are also outlined. Although this is relatively simple to measure in principle, in practice it is extremely difficult to do, for a variety of reasons. Some of these are discussed and the reason why this measurement is particularly problematic with plastic water distribution pipes is illustrated.
Keywords: Acoustic correlation; Water leak detection; Wave propagation